Strategy to Increase the Managerial Effectiveness of Education Foundations in Improving the Quality of Private Education Units - Ruswandi, Iwan; Rubini, Bibin; Sunaryo, Widodo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – This research aims to produce strategies and ways to improve the Managerial Effectiveness of the Chairman of the Board of Education Foundations in Bogor City through strengthening the variables of Organizational Culture, Leadership Serving, and Personality as independent variables and the variables of Commitment to the Organization as intervening variables. Methodology/approach –This study used a mixed methods approach, combining both numbers (quantitative) and descriptive data (qualitative). Surveys were given to foundation chairpersons and school principals to collect information. The data were analyzed using path analysis to see how different factors affect managerial effectiveness. Then, SITOREM analysis was used to find out which areas need improvement. Findings –It was found that that organizational culture, servant leadership, personality, and Commitment to the Organization all have a direct and positive impact on managerial effectiveness. Organizational culture, servant leadership, and personality also positively influence Commitment to the Organization. The SITOREM analysis identified 14 areas that need improvement to strengthen managerial effectiveness, include Empathy, Organizational Stewardship, teamwork, Stability, outcome orientation, training, Work Experience, maintaining the organization’s reputation, career development, self-confidence, productivity, governance, and interpersonal relationships. Novelty/value – This study focuses on the leadership of educational foundation chairpersons, which is rarely studied, especially in Indonesia’s school-level education. This research offers a new model that links organizational culture, servant leadership, personality, and commitment to managerial effectiveness.